ANALYSIS ON POTENTIAL FOR HUMAN ERROR OF WORKERS AS A CAUSE OF THE ACCIDENT AT THE PRODUCTION PROCESS IN METAL CASTING FACTORY PT.X - SENO PRADIPTA (NIM : 25313009), ARYO
Metal casting industry is one of the industrial sectors with a high accident rate level. Data from OSHA (2013) shows the average rate level of accidents and injuries in the metal casting industry by 11.3 per year occupies three major sectors that have an average of the highest accident rate. Human error factor (human error) in the production process of metal casting is one of the main factors causing the accident in metal casting industry (Hsu, 1999). Human Reliability Assessment (HRA) was used to analyze the level of human reliability of an event due to human error (Spurgin et al, 1987). The results using the SHERPA method showed that the potential for human error due to the error action by 48 potential errors, then the value of human reliability (HRI) using methods HEART value of between 0.1 to 0.9 throughout the melting department the lowest value found at melting area with 0,13 HRI. In this study hazards found in the melting department is due to the engine, the lack of improvement of machine safety components, the narrowness of the study, exposure (heat, dust, smoke, ash, and rays), and fire. The caused of human error is management factor, the labor factor, environmental factors and equipment factors. Recommendations for improvement of human error is the improvement of the management and supervisory level monitoring component, additions engine overhaul, as well as the addition or improvement of visual display.